New Fermi smearing approach for scattering of multi-GeV electrons by nuclei - Mariano, Alejandro Edgardo (2004)
The cross section for electron scattering by nuclei at high momentum transfers is calculated within the Fermi smearing approximation (FSA), where binding effects on the struck nucleon are introduced via the relativistic Hartree approximation (RHA). The model naturally preserves current conservation, since the response tensor for an off-shell nucleon conserves the same form that for a free one but with an effective mass. Different parameterizations for the inelastic nucleon structure function, are analyzed. The smearing at the Fermi surface is introduced through a momentum distribution obtained from a perturbative nuclear matter calculation. Recent CEBAF data on inclusive scattering of 4.05 GeV electrons on ⁵⁶Fe are well reproduced for all measured geometries for the first time, as is evident from the comparison with previous calculations.